Analisis Pengaruh Positioning Dan Promosi Terhadap Keputusan Pembelian - Muafa, Irfan Wildzan; Syahrul, Syahrul (Universitas Musamus,Merauke,Papua, 2023)
The problem in this research is the lack of application of positioning and limitations in promoting the product. This study aims to determine the effect of positioning and promotion on purchasing decisions at Planet Distro Merauke Stores. The population used amounted to 2,548 samples used 96 respondents, the method in this study is quantitative research, the data sources used are primary and secondary data while data collection techniques include observation, questionnaires, interviews, and literature studies. Measurements in this study using Likert scale measurements and using SPSS version 26 program with the analytical method used is the method of multiple linear regression analysis. The results of this study indicate that positioning has a significant and positive effect on purchasing decisions who buy products at the Planet Distro Merauke Store, as seen from the value of tcount 30.345 > ttable 1.661. Promotion has a significant and positive effect on purchasing decisions who buy products at the Planet Distro Merauke Store, seen from the tcount 6.791 > ttable 1.661. Positioning and promotion have a significant and positive effect on purchasing decisions who buy products at the Planet Distro Merauke Store, seen from the Fcount 793.656 > Ftable 3.09.